IMPLEMENTASI LOGIKA FUZZY METODE MAMDANI PADA PREDIKSI BIAYA PEMAKAIAN LISTRIK (STUDI KASUS: KELURAHAN GANDASARI, KOTA TANGERANG) - Ema Julpia Aenun; Mashuri Mashuri (Universitas Negeri Semarang, 2022)
Electricity is a very important need for human life. The rapid development of technology makes various activities and equipment more modern which can only run with electricity. The higher the use of electricity will certainly have an impact on the cost of electricity consumption. The cost of using electricity is a problem that contains uncertainty. Fuzzy logic is one of the decision support systems that can be implemented for uncertainty problems. The purpose of this study is to implement the Mamdani method of fuzzy logic in the prediction of electricity consumption costs and obtain accuracy results from the implementation of the fuzzy logic. The input variables used are house area, electronic equipment used, electrical power, and economic income. Also, the output variable used is the cost of electricity consumption. The Mamdani method is also called the Min-Max method which requires 4 stages to obtain the output. This research will be carried out with the help of Matlab software because there are various tools for the Mamdani method. Based on the results of the implementation of the Mamdani fuzzy logic method on the prediction of electricity consumption costs, the MAPE value is 19.60%, which means that it has a truth value of 80.40%. This shows that the fuzzy logic of the Mamdani method is good for predicting the cost of electricity consumption in Gandasari Village, Tangerang City.